Pengaruh Problem Based Learning Terhadap Kemampuan Bernalar Kritis Siswa pada Mata Pelajaran PAI di SMAN 5 Tangerang Selatan - Siti Assyifa Qolbi; Lismawati; Ahmad Mulalic (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to find out how problem-based learning influences students' critical reasoning abilities in PAI subjects at SMAN 5 South Tangerang. This research focused on class X students at SMAN 5 South Tangerang. The focus of this research is faith in angels using descriptive questions on critical thinking skills tests used in data collection procedures. Researchers conduct quantitative research using an experimental approach. The research used a pretest-posttest control group design. The samples used were 30 control group students (class X1) and 30 experimental group students (class X2). While analyzing the data, t test was used. The experimental class outperformed the control group in every category and in critical reasoning. The data is normally distributed and H0 is accepted with the Sig Kolmogorov-Smirnova test result for the data class which is 0.200. In the control class the proportion was 75.70%, but in the experimental class it was 85.50%. The critical reasoning skills of PAI subjects at SMAN 5 South Tangerang are influenced by the Problem Based Learning learning paradigm. Data analysis using the t test obtained a t-test value (Sig.) 0.000.